Beg, borrow, or steal: determinants of student academic misconduct in Ukrainian higher education. Issue 1 (2nd January 2019) - Denisova-Schmidt, Elena; Prytula, Yaroslav; Rumyantseva, Nataliya L.
ABSTRACT: Actions underpinned by the lack of academic integrity are increasingly impacting academic processes within the higher education sector around the world. Bribery, plagiarism and other forms of deception that enable students to obtain undeserved grades or degree certificates undermine the purpose and mission of higher education. By drawing on a representative study conducted among 600 students in Ukraine, this paper explores the determinants of several forms of student academic misconduct and provides insights as to which groups of students are more likely to engage in either monetary or non-monetary corruption. Findings show the importance of student's individual variation in one's levels of general corruption perception and moral stance on corruption, as well as the practical constraints on one's time, living conditions, willingness to study independently, gender and size of the city of origin. While paper focuses only on corruption with direct student involvement, it also outlines a research agenda by discussing the importance of second-order corruption, as well as the role of faculty members and administration in student academic misconduct. Findings will be useful for educators, policymakers and other practitioners.